Assessing The River Water Quality of Sungai Masai, Johor by Using Water Quality Index (WQI) - Aiesha Jamal, Nur Zatul; Mohd Arif Rosli,; Abdul Rahman, Mohammad Ashraf (Journal of Advanced Industrial Technology and Application, 2023)
The water quality problem has begun to receive significant attention from society in Malaysia as the water pollution issue has arisen over the years. Thus, determining the status of raw water quality is crucial to ensure the level of raw water quality has met the usable standard. This study aimed to identify the land activities near the Sungai Masai, Johor. Then, determine the water quality parameter of Sungai Masai, Johor and classify it according to the Water Quality Index (WQI) Malaysia. Complete characterization and classification of the water quality were compared with the standard from the Department of Environment (DOE) for Sungai Masai and were determined by conducting an experiment. Results show that water quality under three different types of land activities around Sungai Masai can be classified as Slightly Polluted or Class III, with WQI values ranging from 59.34 to 74.47. It can be concluded that the surrounding area around Sungai Masai has led this river to be highly contaminated. However, water from Sungai Masai can be used as drinking water, but it requires further treatment before consumption. The water was suitable only for fishery activities and agricultural irrigation if untreated. To improve the quality of research, the parameter for heavy metals should be conducted in the Industrial area to determine whether industrial waste may end up accumulating in the soil and sediment of water bodies or not